Dr Voon's ServEx Scale wins gold medal - Joseph, Corina; Pereira, Helen; Ramli, Atikah; Chiew, Fei Ha; Jack, Suriani; Abu Samah, Aizimah (Universiti Teknologi MARA, Sarawak, 2007)
ServEx Scale, a multi-item measurement tool, is used to diagnose the service excellence orientation of a service organisation as perceived by both the customers and employees via surveys. It consists of six components which outline the various critical requirements for service organizations to achieve service excellence. Rigorous methodological tests indicate that this 32- item scale demonstrates good reliability as well as content, construct and criterion validities in the service organisations context.